Equality, Freedom, Education - Gil, José María (Pensamiento. Revista de Investigación e Información Filosófica, 2024)
Perhaps one the most important and the most difficult problems of the XXI century, after the very urgent problem of the avoidance of atomic war, is the task of finding ways of organizing society which will reconcile the personal and cultural freedom of the individual with the development of an efficient organization of state and economy. By means of a common curriculum, education can help us to begin to solve such urgent problem. Curriculum development is based on tense relationships, for example the tension between the standard language and the regional or social varieties, or the tension between labor demand and vocation. However, such relationships are not irreconcilable. On the contrary, they involve a virtuous tension between equality and freedom, the two great values that must be preserved and strengthened in order to reach happiness.